Blood pressure and fasting glucose changes in male migrants waiting for an asylum decision in Italy. A pilot study. (15th June 2020) - Modesti, Pietro Amedeo; Scali, Edoardo; Marzotti, Ilaria; Ulivi, Nicoletta; Boddi, Maria; Galanti, Giorgio; Pellegrino, Alessio; Macrí, Roberto; ,
Abstract: Background: The Central Mediterranean route from Libya to Italy has been for years the major port of entry from Africa to Europe. However, information on the early effects of permanence in Italy on cardiovascular risk factors is limited. Therefore, the association between length of stay in Italy and blood pressure or blood glucose was explored in young asylum seekers. Methods: Cross-sectional study performed on male asylum seekers (aged 18–40 years), hosted for 0–30 months in Prato, Italy. Blood pressure and blood glucose, measured with validated instruments, were classified according to European Society of Hypertension and American Diabetes Association guidelines respectively. The relationship of quartiles of months of stay in Italy (independent variable) with blood pressure and fasting glucose was investigated with multivariate linear regression adjusted for years of age, world area of origin, education level, travel duration in months, smoking habit, alcohol use, body mass index, triglycerides. Results: On average, the 217 asylum seekers lived in Italy for 8.4 months (95% CI 7.5–9.3; range 0–30 months). At multivariate adjusted linear regression analysis, quartiles of months in Italy were associated with a forward shift in the blood pressure categories of the European Society of Hypertension (B = 0.396; 95% CI 0.190 to 0.602) and in the categories fasting glucose levels of the American Diabetes Association (B = 0.450; 95% CI 0.023 to 0.876). Conclusions: When considering the importance of high blood pressure and type 2 diabetes for ethnic minorities living in Europe, changes of cardiovascular risk factors in the new environment probably need more attention. Highlights: The central Mediterranean route is the main entry route to Europe for migrants. Months after arrival in Italy are associated with an increase in blood pressure. A forward shift in blood pressure and fasting glucose categories is documented. A high degree of surveillance on these fragile populations is needed.